Strengthening Ngledoksari Village, Tawangmangu, Karanganyar as a Disaster-Resilient Village Through a Landslide Early Warning System - Marzuki, Ahmad; Munandar, Choirul Singgih; Ekaputra, Muhammad Raihanriza; Nisya, Saidatul; Pratiwi, Isnaini Intan; Rafi, Muhammad; Desandi, Akmal; Rizqy, Miftahul; Wang, Jasson Franklyn; Hidayah, Maulina Nurul; Al Mutawakil, Hana Syahidah; Meili, Sunti Nur; Neineza, Nania Riswanda; Faruq, Alfan Umar; Fausta, Devara Ega (Indonesian Journal of Community Empowerment (IJCE), 2026)
Ngledoksari Village is one of the landslide-prone areas in Karanganyar Regency due to its hilly geographical location, many steep slopes, and high rainfall. This community service activity aims to strengthen community preparedness in facing landslide disasters through the implementation of Early Warning System (EWS) technology. The method used is Participatory Action Research which includes location surveys, installation, socialization and training on the use of tools to the community. The results of the activity are the installation of EWS tools at several strategic points, namely in Tegalsari Village & Nglurah Village Border. In addition, the socialization process shows an increase in community understanding regarding disaster mitigation and the ability to respond to early warnings independently. It is hoped that the installed EWS tools can be an effective solution to strengthen community-based disaster warning systems in landslide-prone areas